Rancang Bangun Mesin Pengemasan Pupuk Kompos Limbah Penyulingan Minyak Kayu Putih Berbasis Sistem Kendali PLC - Maulana, Ade; Rahmat, Saepul; Prima Dewi, Riyani (Infotekmesin, 2025)
Ujungmanik Village has a eucalyptus oil distillery with essential oil products produced of 100 kg per year. The problem is that the waste from the eucalyptus oil distillation, in the form of twigs and leaves from the eucalyptus oil distillation, accumulates and reduces the production area. The purpose of this study was to design a eucalyptus waste compost fertilizer packaging machine with the addition of a load cell sensor. The method used in making this compost fertilizer packaging machine is a PLC control system for the packaging section and ESP8266 is used to control the load cell sensor for weighing during the packaging process. The test results show that the eucalyptus oil distillation waste compost fertilizer packaging machine based on the PLC control system is capable of packaging 1000-gram organic fertilizer by the load cell sensor and is capable of packaging 10 plastic bags. Based on the monitoring results through the Blynk application, the packaging has an average value of 994.1 grams and an error percentage of 2.1%